2020
DOI: 10.1073/pnas.2007249117
|View full text |Cite
|
Sign up to set email alerts
|

Universal vote-by-mail has no impact on partisan turnout or vote share

Abstract: In response to coronavirus disease 2019 (COVID-19), many scholars and policy makers are urging the United States to expand voting-by-mail programs to safeguard the electoral process. What are the effects of vote-by-mail? In this paper, we provide a comprehensive design-based analysis of the effect of universal vote-by-mail—a policy under which every voter is mailed a ballot in advance of the election—on electoral outcomes. We collect data from 1996 to 2018 on all three US states that implemented universal vote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 19 publications
0
43
1
2
Order By: Relevance
“…Among voters, prior research has shown little party divide on voting by mail, with nearly equal percentages of voters in both parties choosing to vote this way in past studies (4,5). Has a divide emerged this year in how voters aligned with the Democratic and Republican parties want to cast a ballot?…”
mentioning
confidence: 99%
“…Among voters, prior research has shown little party divide on voting by mail, with nearly equal percentages of voters in both parties choosing to vote this way in past studies (4,5). Has a divide emerged this year in how voters aligned with the Democratic and Republican parties want to cast a ballot?…”
mentioning
confidence: 99%
“…An important first step in any effort to understand the correlates of VBM ballot rejection is considering who is likely to request and vote a mail ballot in the first place. Some scholars find that allowing VBM voting leads to considerable turnout effects (Richey 2008;Southwell and Burchett 2000); others, though, find small and sometimes negative effects of VBM on turnout (Dubin and Kalsow 1996;Oliver 1996;Karp and Banducci 2000;Fitzgerald 2005;Kousser and Mullin 2007;Southwell 2009;Bergman and Yates 2011;Gronke and Miller 2012;Gerber, Huber, and Hill 2013;Burden et al 2014;Barber and Holbein 2020;Thompson et al 2020). To the extent that there is a consensus in the literature, it is that VBM has positive albeit modest turnout effects.…”
Section: Who Votes By Mail?mentioning
confidence: 99%
“…There are times at which party mobilization efforts can affect the methods with which voters cast their ballots (Michelson 2005;Herron and Smith 2012;Hassell 2017). However, the most recent and comprehensive studies of the political consequences of VBM voting find no evidence of overall partisan effects or effects of this form of voting on election outcomes (Barber and Holbein 2020;Thompson et al 2020).…”
Section: Who Votes By Mail?mentioning
confidence: 99%
See 2 more Smart Citations